Hb Q-Thailand heterozygosity unlinked with the (-α4.2/) α+-thalassemia deletion allele identified by long-read SMRT sequencing: hematological and molecular analyses - Qin, Danqing; Wang, Jicheng; Yao, Cuize; Bao, Xiuqin; Liang, Jie; Du, Li (Hematology (Luxembourg), 2023)
In the present study, two unrelated cases of Hb Q-Thailand heterozygosity unlinked with the (-α 4.2 /) α + -thalassemia deletion allele were identified by long-read single molecule real-time (SMRT) sequencing in southern China. The aim of this study was to report the hematological and molecular features as well as diagnostic aspects of the rare manifestation. Hematological parameters and hemoglobin analysis results were recorded. A suspension array system for routine thalassemia genetic analysis and long-read SMRT sequencing were applied in parallel for thalassemia genotyping. Traditional methods, including Sanger sequencing, multiplex gap-polymerase chain reaction (gap-PCR) and multiplex ligation-dependent probe amplification (MLPA), were used together to confirm the thalassemia variants. Long-read SMRT sequencing was used to diagnose two Hb Q-Thailand heterozygous patients for whom the hemoglobin variant was unlinked to the (-α 4.2 /) allele for the first time. The hitherto undescribed genotypes were verified by traditional methods. Hematological parameters were compared with those of Hb Q-Thailand heterozygosity linked with the (-α 4.2 /) deletion allele in our study. For the positive control samples, long-read SMRT sequencing revealed a linkage relationship between the Hb Q-Thailand allele and the (-α 4.2 /) deletion allele. Identification of the two patients confirms that the linkage relationship between the Hb Q-Thailand allele and the (−α 4.2 /) deletion allele is a common possibility but not a certainty. Remarkably, as it is superior to traditional methods, SMRT technology may eventually serve as a more comprehensive and precise method that holds promising prospects in clinical practice, especially for rare variants.